Combinational modulations of NiSe2 nanodendrites by phase engineering and iron-doping towards an efficient oxygen evolution reaction. Issue 16 (17th April 2020) - Zhou, Jun; Yuan, Liwei; Wang, Jingwen; Song, Lingling; You, Yu; Zhou, Ru; Zhang, Junjun; Xu, Jun
Abstract : Combinational modulations of phase engineering and heteroatom doping are realized to prepare Fe-doped marcasite NiSe2 nanodendrites, which serve as a superior OER electrocatalyst with improved conductivity and excellent catalytic activity. Abstract : Despite the fulfilling progress in fabricating advanced nickel dichalcogenide catalysts towards an efficient oxygen evolution reaction (OER), previous efforts focused on the pyrite structure. In this work, combinational modulations of metallic NiSe2 nanodendrites by phase engineering and heteroatom doping are achieved to promote the OER. A series of marcasite NiSe2 (m-NiSe2 ) and Fe-doped marcasite NiSe2 (m-Ni1− x Fe x Se2 ) nanodendrites with various dopant contents have been controllably synthesized. On the one hand, phase engineering to synthesize m-NiSe2 nanodendrites offers a better intrinsic electronic conductivity than the pyrite phase. On the other hand, heteroatom Fe doping in m-NiSe2 nanodendrites further gains electronic benefits and simultaneously provides more electrochemical active sites owing to heteroatom displacement defects. Consequently, an optimized catalyst of m-Ni0.94 Fe0.06 Se2 nanodendrites with a moderate dopant content is developed, exhibiting significantly improved OER performance with a low overpotential of 279 mV at 10 mA cm −2, a small Tafel slope of 39 mV dec −1 and long operational stability for 35 h in 1.0 M KOH. In situ surface oxidation of the m-Ni0.94 Fe0.06 Se2 nanodendrites to form amorphous Fe-doped NiOOH/Ni(OH)2 shells during the OER process is demonstrated, which contributes to their superior activity and outstanding stability. This work provides valuable insights into the design of advanced OER electrocatalysts by means of combinational modulations of phase engineering and heteroatom incorporation.